Relation of Pure Tone Odyograms and Prognosis in Sudden Hearing Loss - Gök, Üzeyir; Kapusuz, Zeliha; Sapmaz, Emrah; Yıldız, Mücahit (Fırat University, 2007)
Objectives: To investigate the relation between odyolgical findings and prognosis in patients with sudden hearing loss which were treated in our department. Materials And Methods: Patients files of 54 subjects with sudden hearing loss which were treated in our clinic were researched retrospectively. Steroid,carbogen (%5), urographine, antiviral, complex of vitamin treatments and salness dietary were given to patiens . Response to treatment were researched by daily odyograms. Results: 31 of patiendts were male and 22 of there were female and lefte ar was effected in 32 and right ear in 22 patients.Mean ages of patients were 39.8 (range:17-72). All of the patiends had sudden hearing loss.Whether high frequency sudden hearing loss (descending type) was seen in 17 ears,18 had low frequencies (ascending type), 5 had SHL in all freguencies (flat type) and 14 patients had totaly hearing loss. After treatment, recovery were observed in 35 ears (64.82%), but not recovery in 19 ears (35.18%) were not observed. Treatment was started in the first week of hearing loss in 36 patients (66.66%) and 24 of themes were recovered. 7 of 12 patients (58.30%) in this subjects who were not recovered had totaly hearing loss. 10 of 18 patents whose treatment were started after 7 days were recovered. 18 of 54 patients (61.11%) had vertigo and 11 patients with vertigo were recovered. 39 patients had tinnitus and 25 (64.11%) of these patients were recovered. Conclusion: We determined that efficacy of treatment of sudden hearing loss in patients ©2007, Firat University, Medical Faculty

Amaç: Ani işitme kaybı (AİK) tanısı ile yatırılarak tedavi edilen olgularda odyolojik bulgular ile prognoz arasında ilişkiyi araştırmak. Gereç ve Yöntem: Kliniğimizde AİK tanısı konup yatırılarak tedavi edilen 54 hastaların dosyaları retrospektif olarak incelendi. Hastalara steroid, karbojen (%5), ürografin, antiviral, vitamin kompleksi ve tuzsuz diyet verildi. Hastaların gün aşırı odyogramları yapılarak tedaviye yanıtları araştırıldı. Bulgular: Hastaların 31'i erkek 23'ü bayan olup 22'inde sağ 32' sinde sol kulak etkilenmişti. Yaşları 17 ile 72 arasında olup yaş ortalamaları 39.8 idi. Hastaların tümünde AİK tek taraflı idi. AİK 17 kulakta işitme kaybı yüksek frekansları tutarken (inen tip), 18 kulakta düşük frekansları (çıkan tip), 5 kulakta tüm frekansları (düz tip) tutan ve 14 kulakta ise total işitme kaybı vardı.Tedavi sonucunda 35 (%64.82) kulakta iyileşme elde edilirken 19 (%35.18) kulakta da iyileşme izlenmedi. Hastaların 36'sında (%66.66) ilk hafta içerisinde tedaviye başlandı ve 24 (% 66.66) hastada iyileşme kaydedildi. İlk hafta içerisinde başvuran ve tedaviye başlananlar içinde iyileşme olmayan 12 hastanın 7 sinde ( %58.30) total işitme kaybı mevcuttu. İlk haftadan sonra tedaviye başlanan 18 işitme kayıplı hastanın 10 unda ( %55.55) iyileşme gözlendi. Toplam 54 hastanın 18 inde (% 33.33) vertigo vardı, vertigolu hastalardan 11'i (% 61.11 ) iyileşti. 39 ( %72.22 ) tanesinde tinnitus vardı, bunlardan 25 ( %64.11) i iyileşti . Sonuç: Tüm frekansları tutan veya total işitme kayıplı hastalarda verilen tedavinin etkinliğinin az, yüksek veya düşük frekansları tutan ve tinnitusun eşlik ettiği hastalarda tedavinin etkinliği daha iyi olduğunu tespit ettik. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Ani İşitme Kaybında Saf Ses Odiyogram Tipleri ile Prognoz Arasındaki İlişki